Education and training in public health: is there progress in the European region?. (25th November 2019) - Laaser, Ulrich; Bjegovic-Mikanovic, Vesna; Vukovic, Dejana; Wenzel, Helmut; Otok, Robert; Czabanowska, Katarzyna
Abstract: Background: The Association of Schools of Public Health in the European Region (ASPHER) is confronted with challenges to improve education for public health professionals. In this article, we attempt to answer the question: Did ASPHER members improve their organization and programmes to enable their graduates to acquire the competences to tackle the diverse areas of public health defined in the Ten Essential Public Health Operations (EPHOs)? Methods: ASPHER run two surveys among its membership: In 2011, 66 Schools and Departments of Public Health (SDPHs) took part (82.5%), while in 2015–16, 78 SDPHs (81.3%). The performance of graduates was estimated using a Likert scale. Results: In 2015–16, the SDPHs delivered 169 academic programmes (2.2 on average per SDPH). Among the SDPHs participating in both surveys, significant differences could not be determined, neither for the organization (except increasingly using social media) nor for teaching areas. The performance of graduates did not show significant differences except for the deterioration of EPHO-8 ('assuring sustainable organizational structures and financing'). However, the qualitative data revealed progressive dynamics regarding innovations in the organizational set-up, digitalization, teaching/training, introduction of new modules and research. Conclusions: The results generated do not allow us to state that the innovative elements introduced after the first survey in 2011 have had a clear impact reflected in the second survey carried out in 2015–16, but perhaps this is due to the need for a broader follow-up in order to objectify the potential consequences derived from the boost generated by the changes introduced.